Competitive youth athletes: are they choosing between God and sports? - Livingston, Jennifer (International journal of children's spirituality, 2020)
Competitive youth athletes have demanding schedules that require prioritising regular family activities. Specifically, Christian families often choose to skip church services to attend athletic events. Parents and competitive youth athletes from across the United States were invited to complete surveys which explored youth athletes’ and their parents’ perceptions of the competitive sport environment, the child’s level of spirituality, and the influence of church attendance on the child’s spirituality. The results suggested the parents were aware of the child’s experiences in sport and involvement in church, but they were not aware of the child’s level of reliance on faith to cope with the demands of sport. Additionally, there was no difference in spirituality levels of children regardless of how frequently they attended church. The implications of the study are that Christian youth athletes use their faith to overcome challenges of competition, and factors outside of church attendance contribute to a child’s spiritual development.